Control of cascade boost converters - Lam, Evelyn Wen Lin (2019)
This report presents the design, implementation and control of a cascade boost converter in the presence of a load, reference voltage and input voltage changes. Experimental and simulation results are presented to illustrate the features of the converter system. Both voltage mode and hysteresis based sliding-mode controllers are used in the regulation of the converter. Discussion would be made on the performance of the implemented controller.